2011
DOI: 10.1128/mcb.05237-11
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Heat Shock Factor 1 Molecular and Cellular Targets during Embryonic and Adult Female Meiosis

Abstract: Heat shock factor 1 (HSF1), while recognized as the major regulator of the heat shock transcriptional response, also exerts important functions during mammalian embryonic development and gametogenesis. In particular, HSF1 is required for oocyte maturation, the adult phase of meiosis preceding fertilization. To identify HSF1 target genes implicated in this process, comparative transcriptomic analyses were performed with wild-type and HSF-deficient oocytes. This revealed a network of meiotic genes involved in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 65 publications
1
23
0
Order By: Relevance
“…However, there is now increasing evidence from a number of biological systems that HSF1 is important for diverse “non-stress” conditions including development [26, 40], energy metabolism [27], programmed cell death [41, 42] and carcinogenesis [28, 43]. For these non-heat shock conditions, the transcriptomes regulated by HSF1 are distinct from that of acute heat shock [26, 40]. It is, therefore, important to understand mechanistically how HSF1 regulates these alternative transcriptional programs to influence long-term cellular health.…”
Section: Hsf1 Directs Transcriptional Programs That Are Uncoupled Fromentioning
confidence: 99%
“…However, there is now increasing evidence from a number of biological systems that HSF1 is important for diverse “non-stress” conditions including development [26, 40], energy metabolism [27], programmed cell death [41, 42] and carcinogenesis [28, 43]. For these non-heat shock conditions, the transcriptomes regulated by HSF1 are distinct from that of acute heat shock [26, 40]. It is, therefore, important to understand mechanistically how HSF1 regulates these alternative transcriptional programs to influence long-term cellular health.…”
Section: Hsf1 Directs Transcriptional Programs That Are Uncoupled Fromentioning
confidence: 99%
“…This broad effect of HSF1 on transcription suggests that HSF1 is involved in balancing core cellular processes during stress and enables their rapid reestablishment once conditions suitable for proliferation have been restored. Importantly, HSF1 controls a distinct set of target genes in cell stress, development and cancer progression, and has radically limited capacity to bind to condensed chromatin (Å kerfelt et al, 2010b;Le Masson et al, 2011;Mendillo et al, 2012;Vihervaara et al, 2013). These recent findings highlight the plasticity of HSF1 as a transcriptional regulator, and imply that the HSF1-driven transcription strongly depends on the cell type, developmental state, metabolic conditions and the phase of the cell cycle (see poster).…”
Section: Perspectivesmentioning
confidence: 99%
“…In mice, HSF1 is a maternal factor that is required for gametogenesis and formation of sensory epithelium (Å kerfelt et al 2006). Importantly, the developmental functions of HSF1 are mainly executed through target genes that are unrelated to HSPs, and studies in Drosophila have shown that HSF1 is activated differently in development as compared to in stressed cells (Å kerfelt et al, 2010b;Fujimoto et al, 2004;Jedlicka et al, 1997;Le Masson et al, 2011;Takaki et al, 2006). In cultured cells, HSF1 is stably expressed but, in the context of entire animals, its expression level and subcellular localization vary depending on the tissue and the developmental state (Fiorenza et al, 1995;Å kerfelt et al, 2010b).…”
Section: The Role Of Hsf1 In Dividing Cellsmentioning
confidence: 99%
“…However, these observations have not addressed whether the activation of chaperone gene expression by HSF1 during development corresponds to a distinct regulatory process or a variant of the HSR. Furthermore, genomic analyses in mouse oocytes and testes have identified HSF1 target genes unrelated to HSPs as executors of HSF1 developmental function (Akerfelt et al 2010b;Le Masson et al 2011). Similarly, many of the HSF2 and HSF4 target genes that are crucial for development of cortex and sensory organs, respectively, do not correspond to classical HSP genes (Chang et al 2006;Takaki et al 2006).…”
mentioning
confidence: 99%